Fine Control of Perovskite Crystallization and Reducing Luminescence Quenching Using Self‐Doped Polyaniline Hole Injection Layer for Efficient Perovskite Light‐Emitting Diodes. (18th December 2018) - Ahn, Soyeong; Park, Min‐Ho; Jeong, Su‐Hun; Kim, Young‐Hoon; Park, Jinwoo; Kim, Sungjin; Kim, Hobeom; Cho, Himchan; Wolf, Christoph; Pei, Mingyuan; Yang, Hoichang; Lee, Tae‐Woo
Abstract: Organic–inorganic hybrid perovskites (OHPs) are promising emitters for light‐emitting diodes (LEDs) due to the high color purity, low cost, and simple synthesis. However, the electroluminescent efficiency of polycrystalline OHP LEDs (PeLEDs) is often limited by poor surface morphology, small exciton binding energy, and long exciton diffusion length of large‐grain OHP films caused by uncontrolled crystallization. Here, crystallization of methylammonium lead bromide (MAPbBr3 ) is finely controlled by using a polar solvent‐soluble self‐doped conducting polymer, poly(styrenesulfonate)‐grafted polyaniline (PSS‐g‐PANI), as a hole injection layer (HIL) to induce granular structure, which makes charge carriers spatially confined more effectively than columnar structure induced by the conventional poly(3, 4‐ethylenedioythiphene):polystyrenesulfonate (PEDOT:PSS). Moreover, lower acidity of PSS‐g‐PANI than PEDOT:PSS reduces indium tin oxide (ITO) etching, which releases metallic In species that cause exciton quenching. Finally, doubled device efficiency of 14.3 cd A ‐1 is achieved for PSS‐g‐PANI‐based polycrystalline MAPbBr3 PeLEDs compared to that for PEDOT:PSS‐based PeLEDs (7.07 cd A ‐1 ). Furthermore, PSS‐g‐PANI demonstrates high efficiency of 37.6 cd A ‐1 in formamidinium lead bromide nanoparticle LEDs. The results provide an avenue to both control the crystallization kinetics and reduce the migration of In released from ITO by forming OIP films favorable for more radiative luminescence using the polar solvent‐soluble and low‐acidity polymeric HIL. Abstract : Perovskite crystallization kinetics can be finely controlled using a self‐doped conducting polymer as the hole injection layer of perovskite light‐emitting diodes (PeLEDs). Polar solvent‐soluble self‐doped polyaniline facilitates crystallization control by impeding the solvent evaporation from cast perovskite precursor pseudo‐films. The finely controlled crystallization contributes to achieving granular nanograin structure, which can strengthen the exciton confinement for boosting luminescence efficiency of PeLEDs.